2021
DOI: 10.3389/ftox.2021.640183
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Thresholds of Toxicological Concern: A Review

Abstract: The ecological threshold of toxicological concern (ecoTTC) is analogous to traditional human health-based TTCs but with derivation and application to ecological species. An ecoTTC is computed from the probability distribution of predicted no effect concentrations (PNECs) derived from either chronic or extrapolated acute toxicity data for toxicologically or chemically similar groups of chemicals. There has been increasing interest in using ecoTTCs in screening level environmental risk assessments and a computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Sensitivity comparison using CTD models and UFs derivation. The CTD approach has been often used to generate the ecological threshold of toxicological concern values for screening-level risk assessment (Barron et al, 2021), in the present study, we used CTDs to calculate threshold concentrations (e.g., TC5) for sensitivity comparison as in Wang et al (2014), who compared the sensitivity of chemicals to temperate and tropical fish.…”
Section: Fish Embryo Toxicity Tests (Fet) With D Reriomentioning
confidence: 99%
“…Sensitivity comparison using CTD models and UFs derivation. The CTD approach has been often used to generate the ecological threshold of toxicological concern values for screening-level risk assessment (Barron et al, 2021), in the present study, we used CTDs to calculate threshold concentrations (e.g., TC5) for sensitivity comparison as in Wang et al (2014), who compared the sensitivity of chemicals to temperate and tropical fish.…”
Section: Fish Embryo Toxicity Tests (Fet) With D Reriomentioning
confidence: 99%
“…The introduction of the concept of ecological thresholds of toxicological concern (eco-TTC) has resulted from the upgrading of risk assessment procedures in recent years, the aim of which is to establish an exposure level for chemicals beneath which no significant risk to ecosystems is likely [26,27,44,45]. The use of eco-TTC reduces the need for ecotoxicological studies of untested chemicals in cases where it can be demonstrated that the expected exposure is unlikely to exceed a level of concern.…”
Section: Use Of Available Hc5 and Mechanism Of Action For Risk Assessment And Managementmentioning
confidence: 99%
“…In the last few years, the concept of the ecological threshold of concern (eco-TTC) has been proposed as a pragmatic approach useful in screening-level ecological risk assessment [25][26][27]. Indeed, for chemicals with little or no ecotoxicological information, eco-TTC allows identifying the exposure threshold, below which there is a negligible risk for aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent research under a multisector group of the Committee on Animal Alternatives in Environmental Risk Assessment, Health and Environmental Sciences Institute (HESI; 2019) resulted in a curated collection of data (the EnviroTox Database, which is referenced in Plugge et al 2021), an assessment of the implications regarding mode of action (Kienzler et al 2017(Kienzler et al , 2019, and a detailed study on the database itself (Connors et al 2019). In addition, an invited review was recently published in a special issue of Frontiers in Toxicology (Barron et al, 2021). Reference materials related to the background of all concepts explored can be downloaded directly from the EnviroTox website (Health and Environmental Sciences Institute 2019).…”
mentioning
confidence: 99%